In vitro and in vivo modulation of LPS and carrageenan-induced expression of inflammatory genes by amitriptyline - Laleh Rafiee; Valiollah Hajhashemi; Shaghayegh Haghjooy Javanmard (GarVal Editorial Ltda., 2017)
Context: Amitriptyline, a tricyclic antidepressant is used for the management of psychological disorders and various types of pain. In the previous work, it is founded that amitriptyline inhibited the migration of polymorphonuclear (PMN) into the site of inflammation. Aims: To evaluate the effect of amitriptyline on the expression of some inflammatory mediators such as intercellular adhesion molecule (ICAM-1), vascular cell adhesion molecule (VCAM-1), cyclooxygenase 2 (COX2) and inducible nitric oxide synthase (iNOS). Methods: An in vitro model system of LPS-stimulated human endothelial cells and U937 macrophages and also in vivo model of carrageenan-induced paw edema in rat were used. The expression of inflammatory mediator genes was determined by qRT-Real-time PCR. In endothelial cells, soluble forms of ICAM-1 and VCAM-1 were quantified by ELISA. Results: The expression of ICAM-1, VCAM-1, COX2, iNOS, sICAM-1 and sVCAM-1 significantly decreased by amitriptyline. The finding of this study also confirmed that intraperitoneal (i.p.) injection of amitriptyline inhibited carrageenan-induced inflammation in rat paw edema. Conclusions: The results of the present study provide further evidence for the anti-inflammatory effect of amitriptyline. This effect appears to be mediated by down-regulation of inflammatory genes.